Mussel-inspired MgAl-LDH/carbon fiber film modified by polydopamine for highly efficient removal of Pb2+. Issue 6 (December 2021) - Yang, Wenwen; Cai, Weiquan; Zhou, Jingxun; Dang, Chengxiong; Peng, Xiong; Chen, Yiting; Wei, Xingchuan; Bo, Shilin; Liang, Shuling; Luo, Zhijia
Abstract: Inspired by mussel adhesion protein, a carbon paper@polydopamine@magnesium aluminum hydrotalcite (CP@PDA@MgAl-LDH) film with excellent adsorption performance for toxic Pb 2+ was successfully prepared via modification of CP by PDA and PEI, and a followed simple hydrothermal method to precipitate MgAl-LDH nanoflakes on the surface of CP. It was found that the maximum adsorption capacity of the CP@PDA@MgAl-LDH film calculated from the Langmuir model is up to 1223.15 mg/g; its removal efficiency even remains 98.8% of the original value after seven adsorption-desorption cycles. Especially, the PDA and PEI can not only improve the wettability of the carbon fiber, but also act as a stable anchor to immobilize metal ions through coordination reaction, resulting in promoting the growth of MgAl-LDH nanoflakes on the surface of CP. Furthermore, this method can be effectively extended to prepare other LDH films including NiAl-LDH, ZnAl-LDH and CoAl-LDH, indicating that it is a universal method for preparing LDH films with good application prospect in the fields of adsorption and separation. Graphical Abstract: The carbon paper@polydopamine@Magnesium aluminum hydrotalcite (CP@PDA@MgAl-LDH) membrane with excellent adsorption performance for Pb 2+ was successfully prepared via a modification process of CP by PDA and PEI, and a followed simple hydrothermal process. The PDA and PEI not only improves the surface activity and wettability of the CP, but also serves as a stable anchor for immobilizing metal ions via coordination reaction, resulting in the growth of MgAl-LDH nanoflakes on the surface of the CP. This effective and efficient method can be also extended to prepare other CP@PDA@MAl-LDH (M = Ni, Co and Zn) membranes with potential applications in the field of environmental purification. ga1 Highlights: Preparation of Carbon paper@polydopamine@magnesium aluminum hydrotalcite membrane. The membrane shows excellent cyclic adsorption performance for toxic Pb 2+ . Carbon paper modified by polydopamine to improve adhesive property and wettability. Interaction enhancement between the MgAl-LDH and the carbon via the modification. Extension of this method to prepare other MAl-LDHs (M = Ni, Co, and Zn) membranes.